2006
DOI: 10.1016/j.tet.2005.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Lewis and protic acid mediated Nicholas reactions of 3-acetoxycyclohept-1-en-4-ynedicobalt hexacarbonyl: site selectivity of nucleophile incorporation

Abstract: Nicholas reactions on the cation derived from the cyclic allylic acetate alkynedicobalt complex 1 favour the γ-site kinetically for most nucleophiles, with increasing amounts of αproducts in cases with greater nucleophilicity. Some regiocontrol in introduction of a specific nucleophilic fragment is possible by using different nucleophiles. Under conditions where reversibility is possible, the thermodynamically favoured site is exclusively γ- .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…In previous work, Nicholas reactions of cations that are allylic in addition to being propargylic to an alkyne–Co 2 (CO) 6 group have been shown to favor attacks at the γ-site [i.e., the terminus remote to the alkyne–Co 2 (CO) 6 unit] over the α-site for the majority of nucleophiles (with a greater selectivity for lower reactivity nucleophiles), for reasons that are not entirely well-understood. This observation has been found to apply to both acyclic and cyclic systems . Here, this situation is much less straightforward, as the γ-site of 3b is benzylic, whereas the α-site is substantially more hindered than in the literature cases.…”
Section: Resultsmentioning
confidence: 88%
“…In previous work, Nicholas reactions of cations that are allylic in addition to being propargylic to an alkyne–Co 2 (CO) 6 group have been shown to favor attacks at the γ-site [i.e., the terminus remote to the alkyne–Co 2 (CO) 6 unit] over the α-site for the majority of nucleophiles (with a greater selectivity for lower reactivity nucleophiles), for reasons that are not entirely well-understood. This observation has been found to apply to both acyclic and cyclic systems . Here, this situation is much less straightforward, as the γ-site of 3b is benzylic, whereas the α-site is substantially more hindered than in the literature cases.…”
Section: Resultsmentioning
confidence: 88%
“…In summary, the incorporation of two nucleophiles to the Ferrier‐Nicholas pyranosidic system 15 to generate the bis‐functionalized compounds 62 – 65 , must involve the sequential formation of two different vinylogous Nicholas cations (cations generated from dicobalt complexes arising from propargyl‐allyl ether derivatives),, e.g. A , B , (Scheme ), each one reacting at the γ‐ rather than at the α‐position, with the external nucleophiles to provide bis‐functionalized species C (Scheme ) …”
Section: Resultsmentioning
confidence: 99%
“…Some studies dealing with the influence of the nucleophile in its site‐selective incorporation to allylic/propargylic Nicholas‐type cations have appeared 45. 46 In particular, reports from Green’s group on cyclic allylic/propargylic cations have shown that even though the site remote to the alkyne‐Co 2 (CO) 6 moiety (γ‐site, C‐3 substitution in our study) was the kinetically preferred one for most nucleophiles, increasing amounts of α‐products (C‐1 derivatives) were obtained with more nucleophilic reagents 46. Accordingly, the higher nucleophilicity of TMSCN (along with its small size)47 will be responsible for the observed regioselectivity in the formation of 33 .…”
Section: Resultsmentioning
confidence: 99%